Proof-of-concept method to sanitize a feed mill contaminated with Porcine Epidemic Diarrhea Virus - Huss, A. R.; Schumacher, L. L.; Cochrane, R. A.; Poulsen, E.; Bai, Jianfa; Woodworth, Jason C.; Dritz, Steven S.; Stark, Charles R.; Jones, Cassandra K. (My University, 2016)
Porcine Epidemic Diarrhea Virus (PEDV) has been linked to transmission by livestock feed or ingredients. Measures to exclude pathogens, prevent cross-contamination, and actively reduce the pathogenic load of feed and ingredients are being developed. However, research thus far has focused on the role of chemicals or thermal treatment to reduce PEDV RNA in feedstuffs, and has not addressed potential residual contamination within the manufacturing facility that may lead to continuous cross-contamination of finished feeds. The objective of this experiment was to evaluate the use of a standardized protocol to sanitize an animal feed manufacturing facility contaminated with PEDV. Environmental swabs were collected throughout the facility during the manufacturing of a swine diet inoculated with PEDV. To monitor facility contamination of the virus, swabs were collected at 5 decontamination steps: 1) baseline before inoculation, 2) after production of the inoculated feed, 3) after application of a quaternary ammonium-glutaraldehyde blend cleaner, 4) after application of a sodium hypochlorite sanitizing solution, and 5) after facility heat-up to 60°C for 48 h. The feed mill was contaminated and decontaminated 3 separate times for a total of 3 replications. Collected swabs were analyzed via RT-qPCR and categorized by surface (plastic, rubber, concrete, and metal), type (equipment and structural), and zone (1, 2, and 3). Decontamination step, surface, type, zone and their interactions were all found to impact the quantity of detectable PEDV RNA (P < 0.05). As expected, all samples collected from direct feed contact surfaces (zone 1) contained PEDV RNA after production of the contaminated feed. Additionally, all swabs collected directly adjacent to direct feed contact surfaces (zone 2) were positive following production of the contaminated feed. Of the remaining swabs collected (zone 3), outside of zones 1 and 2, 88.9% had detectable RNA, emphasizing the potential role dust plays in cross-contamination of pathogens throughout a manufacturing facility. Application of the cleaner, sanitizer, and heat were effective at reducing PEDV RNA (P < 0.05), but did not completely eliminate it. Specifically, 29.6%, 14.8%, and 7.4% of zone 1 swabs had detectable PEDV RNA after decontamination with the cleaner, sanitizer and heat, respectively, during only replication 2. Due to this, decontamination was repeated with no PEDV RNA detected from subsequent swab collection. These findings do provide a method for facility decontamination of PEDV, however, the use of liquid cleaners, sanitizers, and/or facility heat-up may not be applicable for most commercial feed manufacturing facilities.
Citation: Huss, A. R., Schumacher, L. L., Cochrane, R. A., Poulsen, E., Bai, J. F., Woodworth, J. C., . . . Jones, C. K. (2016). Proof-of-concept method to sanitize a feed mill contaminated with Porcine Epidemic Diarrhea Virus. Journal of Animal Science, 94, 102-103. doi:10.2527/msasas2016-217
Keywords: Pedv; Disinfection; Feed Mill; Agriculture